Use of bitter melon seed oil (Momordica Charantia) to Improve the photoprotective effect of Sunscreen Formulations - Winarti, Lina; Refayani , Ema Prastiwi (Universitas Ahmad Dahlan, 2024)
Bitter melon seed oil (BMSO) was identified as having potential as an anti-UV radiation agent due to alpha-oleo stearic acid, flavonoids, tannins, polyphenols, and phytosterols, which have the potential as antioxidants. Antioxidants are the main protection for the skin from the dangers of solar radiation, making BMSO a good quality if developed in sunscreen cream. This research aims to determine the effect of adding variations in the concentration of BMSO on the physical characteristics and in vitro photoprotective effectiveness of cream of oxybenzone and octyl methoxycinnamate. Sunscreen creams are made with each BMSO concentration of 0%, 6%, 8%, 10%, and 12%. The result shows that the greater the concentration of BMSO added, the lower the viscosity and pH values, the spreadability and SPF (sun protection factor) values of the cream increase, and the %TP (percentage of transmission pigmentation) and %TE (percentage of transmission erythema) become smaller. The best formula is the formula that contains the highest concentration of BMSO (12%). The characteristics of the best formula are a slightly yellowish, soft cream appearance and a slight smell typical of bitter melon. The spreadability value of the best formula cream is 6.6 ± 0.1 cm, pH of 6.57 ± 0.01, and viscosity of 88.3 ± 4.1 dPa.s, SPF value of 24.27 ± 0.28, %TE of 0.931 ±0.084, and %TP of 0.981±0.0001. These results show that BMSO has the potential to be an active ingredient in sunscreen to reduce the negative effects of using synthetic sunscreen, such as allergenic and irritant.